2021
DOI: 10.1001/jamanetworkopen.2021.28757
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 After COVID-19 Screening and Mitigation Measures for Primary School Children Attending School in Liège, Belgium

Abstract: IMPORTANCERecent data suggest a relatively low incidence of COVID-19 among children. The possible role that children attending primary school may play in the transmission of SARS-CoV-2 remains poorly understood. OBJECTIVE To gain a better understanding of the possible role of children in the transmission of SARS-CoV-2. DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study was conducted from September 21 to December 31, 2020, in a primary school in Liège, Belgium, among a volunteer sample of 181 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 19 publications
8
46
0
1
Order By: Relevance
“…Although alternative approaches have been proposed, some of them are easy to perform without the assistance of health care workers, including saliva or throat wash samples. The self-collection of saliva or throat wash also alleviates the demands for supplies of swabs and personal protective equipment [9,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although alternative approaches have been proposed, some of them are easy to perform without the assistance of health care workers, including saliva or throat wash samples. The self-collection of saliva or throat wash also alleviates the demands for supplies of swabs and personal protective equipment [9,14].…”
Section: Discussionmentioning
confidence: 99%
“…The key question is not only the extent to which RNA or proteins are detected in a single sample, but also how effectively infections are detected in a population through the repeated use of a particular test [12]. Non-traumatic self-collected samples such as saliva or throat washes may be extremely valuable options for massive testing if their sensitivity is shown to be sufficient [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that antiviral treatment would be deployed under transmission of a variant similar to delta, with an increased 8 transmissibility of 97% with respect to the ancestral variant [4]. We assumed that children are less likely to develop symptoms than adults but equally likely to become infected [29,30], Table S2. Further, asymptomatic individuals are assumed to be 30% less infectious than symptomatic individuals [31].…”
Section: Main Modelmentioning
confidence: 99%
“…Prevention of infection, even of asymptomatic cases, is extremely important to reduce circulation of virus among children and transmission of infection from children to unprotected adults [ 23 ]. Recent studies have shown that the role of children in transmission of SARS-CoV-2 infection is greater than previously thought [ 24 ]. This does not surprise as with the progressive increase of vaccination coverage and protection among adults, children remain a large group of totally susceptible subjects among whom virus freely circulates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a lower number of SARS-CoV-2 infection among children can limit school closure and related problems, as it has been shown that school closure can cause relevant mental health problems in the pediatric population. Even after few weeks from school closure, depressive symptoms were reported in about 25% of a group of older children and adolescents in China [ 24 ]. Sadness and eating problems were evidenced in most of adolescents in Italy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%